Preparation of magnetic adsorbent-photocatalyst composites for dye removal by synergistic effect of adsorption and photocatalysis. (10th May 2022) - Cheng, Song; Zhao, Saidan; Xing, Baolin; Liu, Yongzhi; Zhang, Chuanxiang; Xia, Hongying
Abstract: Biochar-based magnetic photocatalyst (ZnFe-BC) is successfully prepared by one-pot method using microwave heating for rhodamine B (RB) and malachite green (MG) removal from wastewater. The characterization results show that ZnFe-BC has the properties of adsorption, photocatalytic degradation and magnetism, contributing to RB and MG removal. The adsorption capabilities of RB and MG are 334.89 mg/g and 576.73 mg/g calculated by Langmuir model, respectively. The adsorption data are fitted to the Thomas and Yoon-Nelson model to predict the breakthrough curves of RB and MG in the fixed-bed adsorption. The photodegradation removals of RB and MG are 99.05% and 98.08%, respectively. A good photodegradation performance of ZnFe-BC is attributed to the high adsorption capability of ZnFe-BC, and synergy between biochar and ZnO on ZnFe-BC. The photocatalytic degradation mechanism is investigated by the density functional theory calculation. ZnFe-BC can be quickly recycled from RB or MG solution under extra magnetic field after use. ZnFe-BC still has good removal in binary RB and MG mixture solution. The present work demonstrates a successful example of waste poplar saw dust converting into the sustainable biochar-based magnetic photocatalyst for RB and MG removal from wastewater Graphical abstract: The schematic of dye wastewater removal by the ZnFe-BC. Image 1 Highlights: A magnetic adsorbent-photocatalyst is successfully prepared for dye removal. Magnetic adsorbent-photocatalyst has good high dye adsorption capability by adsorption. Magnetic adsorbent-photocatalyst has good dye removal by photocatalytic degradation. Synergy between biochar and ZnO on magnetic adsorbent-photocatalyst contributes to dye removal.